(untitled) (Revista do Centro de Estudos Portugueses, 2013)
Este ensaio é uma análise de A ordem natural das coisas de Antonio Lobo Antunes, no qual se tenta desentranhar da estrutura formal peculiar da narrativa, os temas do horror, da loucura e da morte abordados no romance. Articulando as significações de fundo e de forma, o ensaio procura mostrar como o romance enfatiza a dimensão trágica da experiência humana, e o choque que essa ênfase provoca quando posta em face do hedonismo superficial predominante no modus vivendi contemporâneo. This essay is an analysis of A ordem natural das coisas, by Antonio Lobo Antunes. It attempts to investigate the particular formal structure of this narrative, focusing on the themes of horror, madness and death, depicted in the novel. Mixing the meanings of the novel´s thematic and its formal structure, the essay intends to show how the novel expresses the tragic side of human experience, and how this emphatic approach is in shock with the comtemporary superficialism typical of our times.